2019
DOI: 10.1111/ecc.13050
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic capacity correlates with health‐related quality of life after breast cancer surgery

Abstract: To investigate the relation of physical functions to health‐related quality of life (HRQOL), physical activity and fatness of patients during breast cancer treatment within 1 year after surgery. We retrospectively reviewed the patients with breast cancer at the cancer rehabilitation clinic within 1 year after surgery. Physical function assessment included aerobic capacity, muscle strength, flexibility and oedema. Physical activity was assessed using the International Physical Activity Questionnaire‐Short Form,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…If a decrease in muscle force is classically observed in patients with breast cancer post‐CT, 36,37 we demonstrated that the reduction in knee extensor muscle force occurred within the first 8 weeks of treatment, emphasizing early skeletal muscle deconditioning. With no reduction in leg skeletal muscle mass during CT, the reduction in muscle force is likely explained by neural alterations 26 .…”
Section: Discussionmentioning
confidence: 64%
“…If a decrease in muscle force is classically observed in patients with breast cancer post‐CT, 36,37 we demonstrated that the reduction in knee extensor muscle force occurred within the first 8 weeks of treatment, emphasizing early skeletal muscle deconditioning. With no reduction in leg skeletal muscle mass during CT, the reduction in muscle force is likely explained by neural alterations 26 .…”
Section: Discussionmentioning
confidence: 64%
“…Aerobic exercise promotes the ability to perform moderate to vigorous ET within the abilities of the respiratory, cardiovascular, and muscular systems to integrate physiological and functional states for a prolonged period of time [ 121 ], which can be accessed via aerobic capacity [ 122 ]. A poor aerobic capacity has been associated with a markedly increased risk of premature death [ 123 ] and the development of several non-communicable diseases [ 124 ], including cancer [ 125 ].…”
Section: Exercise Training As An Intervention For Obesity and Prostate Cancermentioning
confidence: 99%
“…Cardiorespiratory fitness (CRF) improves physical and cognitive function and is associated with a lower risk of cardiovascular disease, 1 diabetes, and cancer 2 ; fewer postsurgical complications 3 ; and improved health-related quality of life. 4 , 5 An expanding body of evidence suggests that CRF can be increased preoperatively, improving postoperative outcomes. 3 , 6 , 7 Surgical recovery increases postoperative oxygen consumption by up to 50% 8 , 9 in response to inflammation and to promote tissue healing.…”
Section: Introductionmentioning
confidence: 99%